Comparative Study towards Junior High School Students’ Mathematical Problem Solving Enhancement using Three Types of Cooperative Learning Models - Saija, Louise M.; Lalihatu, Desti Naisella (11th International Scholars Conference, 2017)
The mathematical problem solving ability of Indonesian students is not high yet. The aim of this study is to see the students’ mathematical problem solving enhancement after three different cooperative learning strategies were implemented, and to compare the results. The research design is comparative study. The samples in this study are three classes of the seventh grade junior high school (SMP) students. The group of students experience different cooperative learning strategy. The first group experience Students Teams Achievement Division (STAD), the second group JIGSAW II, and the third group experience Teams Games Tournament cooperative learning strategy. Comparative study were conducted partially and overall. The study found that there were mathematical problem solving enhancement in those three group of students. Furthermore, there were differences in the students problem solving enhancement among those groups of students, partially and overall.